2022
DOI: 10.1155/2022/1131696
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Glucose Index Was a Predictor of 6-Month Readmission Caused by Pulmonary Infection of Heart Failure Patients

Abstract: Objectives. Insulin resistance is associated with the prognosis of heart failure (HF) patients. The triglyceride glucose (TyG) index is a simple marker of insulin resistance. However, it remains unclear whether the TyG index is associated with the incidence of readmission in patients with HF. Methods. We enrolled 901 patients with completed records on serum triglyceride and glucose in our study. The TyG index was calculated as log (fasting triglycerides (mg/dL) x fasting glucose (mg/dL)/2). There were 310 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Next, Huang et al [31], in their study, included patients with ADHF and found a significantly higher prevalence of LVEF ≤ 40% in the T3 of the TyG index (≥ 9.32) compared with lower T (T1 [< 8.83] and T2 [8.83-9.32]). Shi et al [39] found significantly different LVEF levels among quartiles of TyG in patients with HF, while the observed trend was U-shaped (higher in the Q1 and Q4 of the TyG index). Finally, Sun et al [41] compared LVEF among Q of the TyG index in patients with ischemic HF who underwent elective PCI and found no significant difference among these groups (P = 0.187).…”
Section: Lvef In Different Groups Of Tyg Index In Patients With Hfmentioning
confidence: 94%
See 2 more Smart Citations
“…Next, Huang et al [31], in their study, included patients with ADHF and found a significantly higher prevalence of LVEF ≤ 40% in the T3 of the TyG index (≥ 9.32) compared with lower T (T1 [< 8.83] and T2 [8.83-9.32]). Shi et al [39] found significantly different LVEF levels among quartiles of TyG in patients with HF, while the observed trend was U-shaped (higher in the Q1 and Q4 of the TyG index). Finally, Sun et al [41] compared LVEF among Q of the TyG index in patients with ischemic HF who underwent elective PCI and found no significant difference among these groups (P = 0.187).…”
Section: Lvef In Different Groups Of Tyg Index In Patients With Hfmentioning
confidence: 94%
“…Further, Guo et al [13] found that in patients with CHF and T2DM, the incidence of rehospitalization due to HF in the T3 group was significantly higher than that observed in the T1 group (HR 1.84, 95% CI 1.16 to 2.91). Finally, Shi and colleagues [39], in 901 HF patients, examined the usage of the TyG index as a predictor of the incidence of readmission of HF patients. To this aim, they divided patients into four Q (Q1 to Q4) based on the TyG index and, surprisingly, found that a lower TyG index (< 7.36) independently augmented the risk of 6-month readmission (P = 0.024).…”
Section: The Tyg Index and Outcomes In Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…The TyG index, a combination of these two indicators, still has limited predictive performance in our study. Some cohort studies have shown a nonlinear relationship between the TyG index and the risk of HF rehospitalization [ 59 , 60 ]. Our study observed a similar trend (Additional file, Figure S3 b).…”
Section: Discussionmentioning
confidence: 99%